Investigation of the Ionic Conduction Mechanism in Carboxymethyl Cellulose/Chitosan Biopolymer Blend Electrolyte Impregnated with Ammonium Nitrate - M. S. A. Rani; N. S. Mohamed; M. I. N. Isa (Taylor & Francis, 2024)
Volume: 20 Issue: 6